Disseminated Superficial Actinic Porokeratosis - S Kumari; M Mathur (Nepal Journal of Dermatology, Venereology & Leprology)
A Case Report about a rare Geno dermatosis -Dissamenated Superficial Actinic Porokeratosis is presented.